Impact of educational group strategy to improve clinical and glycemic parameters in individuals with diabetes and hypertension - Teixeira Lima Favaro, Danielli; Sperli Geraldes Marin dos Santos, Natália; Figueiredo Vendramini, Silvia Helena; Castiglioni, Lilian; Sperli Geraldes Santos, Maria de Lourdes (Investigación y Educación en Enfermería, 2016)
Objective. To evaluate the impact of an educational group strategy to improve clinical and glycemic parameters in individuals with diabetes and hypertension. Methods. This descriptive prospective study included 172 individuals living in São José do Rio Preto-SP, Brazil, who were enrolled in a well-integrated educational group called HIPERDIA (Record System for Follow-up of Hypertensive and Diabetic Individuals) coordinated by a qualified multidisciplinary team. We analyzed sociodemographic, anthropometric, clinical, and laboratory data. Data were collected in the first, fifth, and eighth meeting of the educational group. Results. A total of 68.6% of patients were women, 85.4% were white, 64.0% had an incomplete basic education, 47.7% were retired, 79.7% had been diagnosed with diabetes for 6 or more years, 9.9% were smokers, and 9.9% used alcohol. Individuals’ diastolic blood pressure decreased between the fifth and eighth meeting (p<0.05). Between the first and fifth meeting, both fasting glucose levels (p<0.05) and glycated hemoglobin decreased; the latter continue to drop at the fifth and eighth meetings (p<0.001). Anthropometric parameters remained unchanged. Conclusion. The results suggest that an educational group strategy is favorable for controlling diabetes mellitus and hypertension. How to cite this article Favaro DTL, Sasaki NSGMS, Vendramini SHF, Castiglioni L, Santos MLSG. Impact of educational group strategy to improve clinical and glycemic parameters in individuals with diabetes and hypertension. Invest. Educ. Enferm. 2016; 34(2):